Phase formation and electrical characterization of lead-free (1-x)Ba(Zr0.05Ti0.95)O3–xBa(Fe0.5Ta0.5)O3 binary solid solution - Kruea-In C. (2017)
Copyright © 2017 American Scientific Publishers All rights reserved. The properties of the solid solution (1 − x)BZT05–xBFT were investigated. All samples showed a pure perovskite phase indicating a high solubility limit of BFT in BZT. For x ≥ 01, the samples exhibited strong dielectric-frequency dispersion. Increasing BFT enhanced the dielectric constant and the degree of dielectric-frequency dispersion. Very high dielectric constants ( > 35,000 at 1 kHz) were observed for the x ≥ 05 samples at temperatures > 150 C. An obvious change in dielectric behavior was found for the modified sample (x ≥ 0.1). By using the complex impedance spectroscopy, the dielectric behaviour could be explaned in terms of Maxwell–Wagner polarization due to the heterogeneous conduction of the modified samples. The ferroelectric properties of the x > 0.1 samples also presented a large change as compared to the unmodified sample due to these samples had higher leakage current.